COMBINATION OF HIGH-ALKALINE SAMPLE PREPARATION OF SAMPLES WITH ORGANIC MATRIX, FOLLOWED BY CATALYTIC KINETIC DETERMINATION OF TOTAL IODINE IN THE FORM OF IODIDE BY FERUM(III)-NITRITO-THIOCYANATE REACTION: UDC 543.42.062 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Combination of high-alkaline sample preparation of samples with organic matrix, followed by catalytic kinetic determination of total iodine in the form of iodide by ferum (III)-nitro-tiotsianatnoyu reaction was implemented.
Keywords: sample preparation, total iodine, kinetic methods of analysis